1986
DOI: 10.1117/12.949884
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Approach To Characterizing And Presenting Streak Camera Performance

Abstract: This is a preprint of a paper intended for publication in a journal or proceedings. Since changes may be made before publication, this preprint is made available with the un derstanding that it will not be cited or reproduced without the permission of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Tests have shown that the intensity of the halo is two to four orders of magnitude below the peak. 4 Reducing the gap will reduce the halo diameter and increase its brightness. Using a collimator at the screen is a likely method of controlling this problem.…”
Section: Screen Elastic Scatteringmentioning
confidence: 99%
“…Tests have shown that the intensity of the halo is two to four orders of magnitude below the peak. 4 Reducing the gap will reduce the halo diameter and increase its brightness. Using a collimator at the screen is a likely method of controlling this problem.…”
Section: Screen Elastic Scatteringmentioning
confidence: 99%